Human Adaptation to Deep Space Environment: An Evolutionary Perspective of the Foreseen Interplanetary Exploration - François Criscuolo; Cédric Sueur; Audrey Bergouignan; Audrey Bergouignan (Frontiers Media S.A., 2020)
Long-term and deep space exploration is a prevailing dream that is becoming a reality. Is that so? The answer to this question depends on how the main actors of space exploration, i.e., politicians, scientists, and engineers, define "long-term" and the ultimate goals of the current space programs. Presently, long-term refers to few months or years, which is equivalent to the time necessary for a manned mission to reach another planet and return to Earth. Such a space mission is a tremendous scientific challenge associated with multidisciplinary issues spanning from technology to medicine biology, social, and psychological science. It has been a priority of the main westernized societies that has attracted the brightest and most innovative scientific minds since World War II. At first the stakes were mainly political in order to demonstrate to other countries power and strength. It progressively became a scientific motivation to uncover the secrets of the Universe and life's origin, and potentially to find traces of distant life. More recently, a desire to colonize space and exploit resources on other planets has emerged as a new dream. Although the journey to Mars is still a prospective and traveling in deep space a further elusive goal, one can question the ultimate implications of deep space exploration over the long-term.